2005
DOI: 10.1103/physrevb.72.014432
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between spin-density wave and induced local moments inURu2Si2

Abstract: Theoretical model for magnetic ordering in the heavy-fermion metal URu2Si2 is suggested. The 17.5 K transition in this material is ascribed to formation of a spin-density wave, which develops due to a partial nesting between electron and hole parts of the Fermi surface and has a negligibly small form-factor. Staggered field in the SDW state induces tiny antiferromagnetic order in the subsystem of localized singlet-singlet levels. Unlike the other models our scenario is based on coexistence of two orderings wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
81
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 51 publications
5
81
0
Order By: Relevance
“…The presence of this kink, when taken within the context of the analysis of Mineev and Zhitomirsky [15], indicates a scenario where there exists no coupling between the order parameters of the HO state and that of the high-pressure AFM phase, and furthermore suggests that sample impurities or uncharacterized strains may be culpable for the observed moment at low pressures. The persistence of this kink and its static position upon reducing T 0 with increased x is consistent with a vertical or nearly vertical HO/AFM transition occurring at P c =15 kbar; as this transition is indirectly probed, there can be no unambiguous determination as to the degree of its order.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of this kink, when taken within the context of the analysis of Mineev and Zhitomirsky [15], indicates a scenario where there exists no coupling between the order parameters of the HO state and that of the high-pressure AFM phase, and furthermore suggests that sample impurities or uncharacterized strains may be culpable for the observed moment at low pressures. The persistence of this kink and its static position upon reducing T 0 with increased x is consistent with a vertical or nearly vertical HO/AFM transition occurring at P c =15 kbar; as this transition is indirectly probed, there can be no unambiguous determination as to the degree of its order.…”
mentioning
confidence: 99%
“…In an effort to explain the observed properties of URu 2 Si 2 , several microscopic models have been proposed [9,10,11,12,13,14,15]. In addition to the theoretical pursuits, many varied experimental techniques have been employed to confirm and/or constrain the proposed models; however, the experimental results fail to converge upon an encompassing microscopic description of the ordered states of URu 2 Si 2 , but do provide valuable insight when contextually analyzed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We compile in Table 2 a section of the large number of theoretical efforts [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] to interpret the HO phase transition through analytic models and calculations. Note how these have spanned almost 20 years of work.…”
Section: Introductionmentioning
confidence: 99%
“…Two important current lines of inquiry regarding the URu 2 Si 2 T − P phase diagram are how the HO-AFM phase boundary relates to 1) the higher-temperature PM-HO/AFM boundary, which might indicate whether HO and AFM coexist microscopically [23,24], and 2) the lower-temperature SC phase boundary. While some neutron scattering reports concluded that the HO-AFM boundary is separate from the PM-HO/AFM curve [23,25], a more recent report of neutron scattering and ac susceptibility suggested a sharp transition at 7 kbar, consistent with HO-AFM phase separation [26,27], and supported a ∼ 4 kbar SC critical pressure.…”
Section: Introductionmentioning
confidence: 99%